ELECTROCHEMICAL SENSOR FOR ELECTROLYTE SCREENING IN SIMULATED RENAL SAMPLES - Belgis, Belgis; Muhaimin, Muhaimin; Firdaus, Aji Akbar (Journal of Vocational Nursing, 2025)
Introduction: Electrolyte imbalance frequently occurs in patients with chronic kidney disease (CKD) due to impaired renal regulation of ions such as sodium, potassium, chloride, and bicarbonate. Uncorrected abnormalities can lead to cardiac arrhythmias, neuromuscular dysfunction, and increased mortality. Regular monitoring is critical; however, conventional laboratory methods often require complex equipment and are inaccessible in low-resource settings. Electrochemical sensors provide a practical alternative by enabling rapid, direct measurement of electrolytes through electrical signals generated by ion-selective electrodes. Methods: This study presents the development and validation of a drop-casting-based electrochemical sensor designed for detecting sodium (Na+), potassium (K+, chloride (Cl-), and bicarbonate (HCO₃-) ions. The sensor was fabricated using a low-cost and straightforward method and tested with synthetic serum simulating both normal and renal failure conditions. Results: Calibration curves demonstrated strong linearity (R² > 0.93) for all ions, with minimal deviation for Na+ and K+ Performance validation showed acceptable sensitivity and stabilization time (<10 seconds), supporting its potential for point-of-care use. Conclusions: The device is easy to use, portable, and affordable, making it suitable for vocational healthcare workers in primary health centers and home-based care. Despite limitations in bicarbonate detection, the sensor shows promise for early electrolyte screening in decentralized healthcare settings. Further refinement and broader validation are recommended.